Inflation in the G7 Countries: Persistence and Structural Breaks - Guglielmo Maria Caporale; Luis A. Gil-Alana; Carlos Poza (Center for Economic Studies and Ifo Institute (CESifo), 2020)
This paper examines long-range dependence in the inflation rates of the G7 countries by estimating their (fractional) order of integration d over the sample period January 1973 - March 2020. The results indicate that the series are very persistent, the estimated value of d being equal to or higher than 1 in all cases. Possible non-linearities in the form of Chebyshev polynomials in time are ruled out. Endogenous break tests are then carried out, and the degree of integration is estimated for each of the subsamples corresponding to the detected break dates. Significant differences are found between subsamples and countries in terms of the estimated degree of integration of the series.
Keywords: C22; E31; 330; inflation rates; G7; persistence; long memory; long-range dependence